2011
DOI: 10.1002/mrm.23120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of signal formation in local arterial input function measurements of dynamic susceptibility contrast MRI

Abstract: Correct arterial input function (AIF) measurements in dynamic susceptibility contrast-MRI are crucial for quantification of the hemodynamic parameters. Often a single global AIF is selected near a large brain-feeding artery. Alternatively, local AIF measurements aim for voxel-specific AIFs from smaller arteries. Because local AIFs are measured higher in the arterial-tree, it is assumed that these will reflect the true input of the microvasculature much better. However, do the measured local AIFs reflect the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The local AIF methods may minimize the dispersion‐related errors affecting the DSC perfusion quantification process, but on the other hand they are particularly sensitive to partial volume effects . Several methods have been proposed to define a local AIF , but further efforts are still required to validate these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The local AIF methods may minimize the dispersion‐related errors affecting the DSC perfusion quantification process, but on the other hand they are particularly sensitive to partial volume effects . Several methods have been proposed to define a local AIF , but further efforts are still required to validate these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, the signals from arteries show some angular dependence , indicative of a limitation of the simple model considered here. More extensive modeling along the lines of the work in might shed more light on this issue, as well as determining the level of accuracy the proposed correction method can be expected to achieve. This is, however, beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The correction method proposed here relies upon the accurate identification of the AIF, which is widely recognized challenge , particularly due to partial volume effects. Recently methods have been proposed that exploit both magnitude and/or phase images to provide an improved estimate of the AIF. The proposed MV correction method will directly benefit from any such method, because a more accurate AIF should lead to a more accurate MV correction within the proposed Bayesian framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is valid only when the temporal resolution is relatively low and when the entire brain is equally and properly perfused. Taking into account regional variations in blood flow, several studies suggested methods to define and use local AIF (5458). This approach, although not currently accepted as the default method, should be further validated.…”
Section: Introductionmentioning
confidence: 99%